Kōḍēkalla vacanavākya - Basava (Prasārāṅga, Kannaḍa Viśvavidyālaya)
Complete works of a Kannada Lingayat poet
Poems - Vol. 3 has editor: Śivānanda Es. Viraktamaṭha - Kannada in kanares. Schr
Keywords: Kannada; Religiöse Lyrik